Monogenean parasites on the gills of some fish species from lakes Sapanca and Durusu, turkey - (:unkn) unknown (My University, 2009)
Sapanca ve Durusu göllerindeki 11 balık türü; Silurus glanis, Esox lucius, Rutilus rutilus, Vimba vimba, Scardinius erythrophthalmus, Abramis brama, Tinca tinca, Cyprinus carpio, Rhodeus sericeus amarus, Chalcalburnus chalcoides, Rutilus frisii’den Monogenean parazitler çalışıldı. Dactylogyrus, Silurodiscoides, Tetraonchus ve Paradiplozoon genuslarına ait 19 monogenoid türü; Dactylogyrus sphyrna, D. vistulae, D. phoxini, D. difformis, D. difformoides, D. chalcalburni, D. bicornis D. nybelini, D. frisii, D. crucifer, D. cornu, D.cornoides, D. extensus, D. macracanthus, D. izjumovae, Silurodiscoides siluri, S.vistulensis, Tetraonchus monenteron ve Paradiplozoon sp. bulundu. D.bicornis, D.nybelini ve D.izjumovae Türkiye için yeni kayıtlardır.

Monogenean parasites from 11 fish species Silurus glanis, Esox lucius, Rutilus rutilus, Vimba vimba, Scardinius erythrophthalmus, Abramis brama, Tinca tinca, Cyprinus carpio, Rhodeus sericeus amarus, Chalcalburnus chalcoides, Rutilus frisii were examined, from Lakes Sapanca and Durusu, Turkey. Nineteen monogenoid species were found, belonging to four genera; Dactylogyrus, Silurodiscoides, Tetraonchus and Paradiplozoon. These are: Dactylogyrus sphyrna, D. vistulae, D. phoxini, D. difformis, D. difformoides, D. chalcalburni, D. bicornis D. nybelini, D. frisii, D. crucifer, D. cornu, D.cornoides, D. extensus, D. macracanthus, D. izjumovae, Silurodiscoides siluri, S. vistulensis, Tetraonchus monenteron and Paradiplozoon sp. D. bicornis, D. nybelini and D. izjumovae are new records for Turkey.
Sapanca ve Durusu göllerindeki bazı balık türlerinin solungaçlarındaki monogenean parazitler
Keywords: Balıkçılık; Zooloji